The therian sternum at the lateral somitic frontier: Evolution of a composite structure. (6th July 2020) - Buchholtz, E. A.; Yozgyur, Z. M.; Feldman, A.; Weaver, A. A.; Gaudin, T. J.
Abstract: The mammalian sternum plays key roles in structural support, locomotion and ventilation, but its evolutionary history has rarely been addressed. Unlike most other synapsids, the therian presternum lacks a discreet interclavicle, and the mesosternum is composed of a series of sternebrae. Here, CT scans of fossil and living therians are used to confirm that the therian presternum incorporates multiple elements, including the interclavicle and the anteriormost sternal bands of ancestral synapsids. A previously unrecognized transitional element that articulates with rib 1 is variably present and is hypothesized to permit the direct integration of the first rib and the sternum, despite their origins in different developmental domains. Sternebrae are found at sites where primaxial ribs interact directly with the abaxial sternum and locally inhibit skeletal maturation. Both presternal fusion and mesosternal subdivision are the products of small developmental changes that allowed the adaptation of ancestral structures to the lifestyles of therians. Abstract : The mammalian sternum plays key roles in structural support, locomotion and ventilation, but its evolutionary history has rarely been addressed. Here, CT scans of fossil and living therians confirm that the therian presternum incorporates multiple elements, including the interclavicle and the anteriormost sternal bands of ancestral synapsids. A previously unrecognized transitional element that articulates with rib 1 is variably present and is hypothesized to permit the direct integration of the first rib and the sternum, despite their origins in different developmental domains.